Clinical Supervision of Madrasah's Head in MTs Darul Huda Bandar Lampung - Dermawan, Oki; Gumilang, Gumilang (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2020)
The implementation of clinical supervision of madrasah principals aims to shape the performance of educators becoming more professional in carrying out their functions as supervisors. The madrasa head must be able to master his duties and carry out his duties properly, he is responsible for all madrasa activities regulating the teaching and learning process, regulating matters relating to student affairs, business, finance and regulating relations with the community. In a management it is explained that one of the most important aspects in an organization is the way a person leads to the organization being led, a good organization will produce excellent results starting from the structure, human resources, and others. While the nature of leadership is the activity of leading the process of influencing subordinates or others. Formulation of the problem: Based on the background of the problem above, then the problem is "How is the head of the madrasa conducting clinical supervision on improving the performance of educators in MTs Darul Huda Bandar Lampung? " This study uses a qualitative approach to describe the problem and focus of research. Based on the research and analysis,  the researchers concluded that the process of clinical supervision by the headmaster of madrasa at MTs Darul Huda Bandar Lampung, had been carried out. In carrying out their duties the madrasa head has carried out several stages of clinical supervision including the initial meeting stage, the observation stage and the final meeting stage.